Six Party Talks dalam Negosiasi Amerika Serikat dan Korea Utara Terkait Daftar Hitam Negara-Negara Pendukung Terorisme Tahun 2003 – 2008 - Justisiawan, I.G.N. Dwi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2014)
ABSTRACT The purpose of this research is to explain the role of six party talks in United States and North Korea negotiation process. There are many diplomacy issues between United States and North Korea, one of the hot issues that were on discussed was the issue of the inclusion of North Korea in the black list of the state sponsors of terrorism that maked by the United States. Various negotiations have been carried out by the two countries to achieve the mutual agreement, one of the negosiations which that was held between the two countries are the negotiations that involving the six party talks. In this case, I put more emphasis on the role of the six party talks in the negotiations between United States and North Korea to reach a mutual agreement between the two countries. Keywords: negotiations, six party talks, mutual agreement